2001
DOI: 10.1063/1.1355766
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of dissociative adsorption of NH3, PH3, and AsH3 on Si(001)–(2×1)

Abstract: Effect of the cluster size in modeling the H 2 desorption and dissociative adsorption on Si(001)Using a first-principles pseudopotential method we have studied the adsorption and dissociation of NH 3 , PH 3 , and AsH 3 on the Si͑001͒-͑2ϫ1͒ surface. Apart from the existence of a barrier for the adsorption of the precursor state for arsine, we observe that the global behavior for the chemisorption of the XH 3 molecules considered in this work is as follows: the gas phase XH 3 adsorbs molecularly to the electroph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

15
42
2

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(59 citation statements)
references
References 54 publications
15
42
2
Order By: Relevance
“…The dimer elongation is consistent with experimental [29] as well as theoretical [14,15] findings for other small hydrocarbon molecules, while the dimer tilting follows the same pattern observed for the dissociative adsorption processes of other small molecules like XH 3 (X = N, P, and As) [31]. The calculated C-H bond length of $1.10 Å for all the considered models is also in good agreement with early theoretical estimates for other small hydrocarbon molecules and is close to that observed for the free CH 3 OH molecule.…”
Section: Chsupporting
confidence: 89%
“…The dimer elongation is consistent with experimental [29] as well as theoretical [14,15] findings for other small hydrocarbon molecules, while the dimer tilting follows the same pattern observed for the dissociative adsorption processes of other small molecules like XH 3 (X = N, P, and As) [31]. The calculated C-H bond length of $1.10 Å for all the considered models is also in good agreement with early theoretical estimates for other small hydrocarbon molecules and is close to that observed for the free CH 3 OH molecule.…”
Section: Chsupporting
confidence: 89%
“…Extensive theoretical modeling 19,[28][29][30][31][32][33] in conjunction with detailed STM images provided a consistent interpretation of the first stage of this reaction, namely the thermal dissociation of PH 3 into phosphorus and hydrogen adatoms. However, the subsequent incorporation reactions that take phosphorus adatoms into the surface remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…There are a number of publications about the interaction of phosphine with the silicon surface (see [13,14] and citations therein). It has been reported that PH 3 easily adsorbs on (1 0 0) Si; a non-dissociative adsorption of PH 3 on the dangling bonds of the (2 × 1)-reconstructed surface was found at room temperature.…”
Section: Conventional Vapor Phase Doping With Phosphorusmentioning
confidence: 99%